2015
DOI: 10.1111/dmcn.12950
|View full text |Cite
|
Sign up to set email alerts
|

Muscle growth is reduced in 15‐month‐old children with cerebral palsy

Abstract: Aim Lack of muscle growth relative to bone growth may be responsible for development of contractures in children with cerebral palsy (CP). Here, we used ultrasonography to compare growth of the medial gastrocnemius muscle in children with and without CP. Method Twenty‐six children with spastic CP (15 males, 11 females; mean age 35mo, range 8–65mo) and 101 typically developing children (47 males, 54 females; mean age 29mo, range 1–69mo) were included. Functional abilities of children with CP equalled levels I t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
163
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(180 citation statements)
references
References 22 publications
(64 reference statements)
14
163
1
2
Order By: Relevance
“…A reduced PCSA would decrease, rather than increase muscle stiffness. The substantially lower PCSA may be explained by a smaller cross-sectional area of muscle fibers (fCSA) or a lower number of muscle fibers in SP [50, 51]. Using ST biopsies, fCSA was shown to be 32% lower in children with SP compared to TD children [52].…”
Section: Discussionmentioning
confidence: 99%
“…A reduced PCSA would decrease, rather than increase muscle stiffness. The substantially lower PCSA may be explained by a smaller cross-sectional area of muscle fibers (fCSA) or a lower number of muscle fibers in SP [50, 51]. Using ST biopsies, fCSA was shown to be 32% lower in children with SP compared to TD children [52].…”
Section: Discussionmentioning
confidence: 99%
“…Increases in muscle size following strength training may also influence the mechanical properties of the musculotendinous unit. Specific strength training modes lead to muscle growth patterns via preferential increases in muscle fascicle pennation angle (concentric load) versus muscle fascicle length (eccentric load) in TD adults (Franchi et al, 2014), which may have implications for increasing joint range of motion and/or reducing contracture in individuals with CP (Herskind et al, 2015;Willerslev-Olsen, Lorentzen, & Nielsen, 2014).…”
Section: Muscle Morphology and Architecture Outcomesmentioning
confidence: 99%
“…Recent reports have highlighted stunted growth in the lower limb as a contributing factor to contracture development (Gough and Shortland, 2012) and slowed growth rate has been detected as early as 15-months of age (Herskind et al, 2015). Several investigators have described increased passive stiffness of the calf muscle in children with CP and different tests have shown that the calf muscle is 22–120% stiffer in CP children compared to TD (Ross et al, 2011; de Gooijer-van de Groep et al, 2013; Geertsen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%